Implementation of Teaching Games for Understanding Model on Students’ Kasti Skills Heuleut I Public Elementary School Majalengka - Zaki Adib Al Khairi; Encep Sudirjo; Adang Sudrazat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to implement the Teaching Games for Understanding (TGfU) learning model to enhance the kasti playing skills of students at Heuleut I Public Elementary School Majalengka. Teaching Games for Understanding (TGFU) is an instructional model that emphasizes understanding tactics and game strategies rather than solely focusing on the mastery of physical techniques. It is anticipated that this model will encourage students to be more active in the learning process, improve their comprehension of the game, and facilitate comprehensive motor skill development. The study involved 27 fifth-grade students at Heuleut I Public Elementary School Majalengka, including 17 male and 10 female students. This research utilized a Classroom Action Research (CAR) design. Data collection was conducted in two phases: quantitative and qualitative. The success indicator for this study was set at a 90% proficiency rate in students’ kasti playing skills. Pre-cycle observations indicated a skill level of 11.2%. In Cycle I, students’ skill levels improved to 37.1%; in Cycle II, they reached 70.3%; and in Cycle III, they attained 92.6%. The results from Cycle III demonstrated that students achieved the success criterion of 90% proficiency in kasti playing skills. In conclusion, the findings of this study indicate that the application of the Teaching Games for Understanding (TGfU) learning model in kasti instruction significantly enhances the playing skills of fifth-grade students at Heuleut I Public Elementary School Majalengka.